Religious Moderation: From Text to Context Based on Maqasidu Shari'ah - M.Junaidi; Kuswardhani; Achmad Miftah Farid (Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Religious pluralism can be seen from the 5 religions recognized by the Indonesian state, namely Islam, Catholicism, Christianity, Hinduism, Buddhism and Confucianism. Every religion always believes that its religion is the most correct. It is undeniable that Muslims have a big role in Indonesia's independence. It is hoped that the concept of a state of law based on Pancasila maqasidu shari'ah can reduce the desire to establish an Islamic state as Indonesia is a pluralistic nation. The purpose of this study is: How to deradicalize religion with a religious moderation approach based on maqasidu shari'ah. This research method is literature with a qualitative approach. The research method used in this study is content analysis. Content analysis is a study that combines the results of many original, systematic, and planned studies. The data sources in this article are journals and books. Radicalism in understanding religion can potentially lead to extremism. There needs to be a reconstructing on the understanding of the texts of the Qur'an and hadith from textual to more moderate contextual that is relevant to the conditions of the times. In the context of Indonesia, this is very urgent considering that Indonesia is a very pluralistic country, Reconstruction of understanding of the text is not merely a rational and contextual understanding. However, this understanding must be in line with the objectives of Islamic law (maqasidu shari'ah). So, in the context of Indonesia to deradicalize religion, a moderate religious understanding approach is carried out based on maqasidu shari'ah.